Special features of RAD Sequencing data: implications for genotyping. Issue 11 (30th October 2012) - Davey, John W.; Cezard, Timothée; Fuentes‐Utrilla, Pablo; Eland, Cathlene; Gharbi, Karim; Blaxter, Mark L.
Abstract Restriction site‐associated DNA Sequencing (RAD‐Seq) is an economical and efficient method for SNP discovery and genotyping. As with other sequencing‐by‐synthesis methods, RAD‐Seq produces stochastic count data and requires sensitive analysis to develop or genotype markers accurately. We show that there are several sources of bias specific to RAD‐Seq that are not explicitly addressed by current genotyping tools, namely restriction fragment bias, restriction site heterozygosity and PCR GC content bias. We explore the performance of existing analysis tools given these biases and discuss approaches to limiting or handling biases in RAD‐Seq data. While these biases need to be taken seriously, we believe RAD loci affected by them can be excluded or processed with relative ease in most cases and that most RAD loci will be accurately genotyped by existing tools.